Intraoperative Recurrent Laryngeal Nerve Monitoring During Pediatric Cardiac and Thoracic Surgery: A Mini Review - Lawlor, Claire M.; Zendejas, Benjamin; Baird, Christopher; Munoz-San Julian, Carlos; Jennings, Russell W.; Choi, Sukgi S. (Frontiers in Pediatrics, 2020)
Objective: Review techniques for intraoperative recurrent laryngeal nerve (RLN) monitoring during pediatric surgery for esophageal atresia, tracheoesophageal fistula, tracheobronchomalacia, and cardiac surgery. Summary Background Data: Literature was reviewed for reports of intraoperative recurrent laryngeal nerve monitoring in cervical, thoracic, and cardiac surgical procedures which place the RLNs at risk for injury. Methods: Review paper. Results: The RLN is at risk during pediatric surgery for esophageal atresia, tracheoesophageal fistula, tracheobronchomalacia, and cardiac surgery. Intraoperative nerve monitoring has decreased rates of RLN injury in thyroid surgery. Intraoperative RLN monitoring techniques appropriate for pediatric surgery are discussed, including endotracheal tubes with integrated surface electrodes, adhesive surface electrodes for smaller endotracheal tubes, endolaryngeal electrodes, and automatic periodic continuous intra-operative stimulation. Conclusions: Multiple techniques exist to monitor the RLN in children undergoing cervical, cardiac and thoracic surgery. Monitoring the RLN during procedures that place the RLNs at risk may help decrease the rate of RLN injury.